Self-regulation and exercise maintenance in older women - Schneider, Joanne Kraenzle
Evidence of the many health benefits of regular physical exercise continues to accumulate. So convincing is this evidence that the U.S. Department of Health and Human Services listed physical activity and fitness first on its list of goals for the year 2000. While initiation of exercise is problematic for many, maintenance of regular exercise patterns poses an even greater challenge. Of special importance is the prevalence of a sedentary life-style among the growing number of older individuals. Because older individuals incur three times the health care cost of younger individuals, interventions that promote or maintain functional capacity and prevent or lessen the impact of chronic disease will reduce health care expenditures. The purpose of this study was to examine factors that influence exercise maintenance in an older population using the self-regulation of exercise maintenance model which focuses on the individual's personal meaning or interpretations of exercise.{{{{This study was the second of two phases. The aims of Phase I, the preliminary descriptive phase, were to identify episode-specific interpretations of exercise in women, 60 years of age and older, immediately after an exercise episode, and pilot test questions to be used to measure self-reported exerise behavior. Semi-structured interviews were used to identify qualitative descriptors for episode-specific interpretations of exercise. These qualitative descriptors then were used to develop an instrument to measure episode-specific interpretations of exercise for the present study, Phase II. The self-report questions concerning exercise behavior were revised based on responses elicited in Phase I and also were used in this second phase.{{{{In Phase II, instruments that measure general and episode-specific interpretations of exercise were administered to older women (55 years of age and older). The primary aims of this phase were to evaluate the psychometric properties of the newly developed instruments measuring episode-specific and general interpretations of exercise and examine the contribution of episode-specific interpretations, a component of the self-regulation of exercise maintenance model, to the understanding of exercise behavior. Also in Phase II, a fitness subsample of older women were recruited to examine the relationship between self-reported exercise behavior and physiologic indicators of exerise behavior (estimated maximal oxygen consumption and body composition) and examine the relationship between ratings of perceived exertion and heart rates of older women.{{{{Results showed that episode-specific interpretations of exercise accounted for an additional amount of variance after the effects of age and general interpretations of exerise were removed. Future research should include examination of episode-specific interpretations over time to test the self-regulation of exercise maintenance model. In addition, nursing interventions can be developed and tested to restructure episode-specific interpretations of exercise and improve exercise maintenance.{{{{Overall, self-reported exercise behavior, and at best only moderately, related to estimated maximal oxygen consumption. Body compositin was moderately related in the expected direction to self-reported exercise behavior. The relationship between self-reported exercise behavior and functional measures or measures of activities of daily living should be examined in future studies.{{{{Correlations between perceived exertion and heart rates of older women, for the most part, were strong and positive (the expected direction). However, four women had a negative relationship between perceived exertion and heart rate. Additional work is needed to examine the relationship between heart rate and perceived exertion in older women especially with regard to external variables such as anxiety.